A bioinspired, electroactive colorable and additive manufactured photonic artificial muscle. Issue 8 (2nd February 2022) - Ma, Wentao; Li, Bo; Jiang, Lei; Sun, Ya; Wu, Yehui; Zhao, Pengfei; Chen, Guimin
Abstract : A structure-colorable flexural artificial muscle (FlexAM) is developed by integrating both a flexible two-dimensional grating pattern layer and dielectric elastomers  via  additive laminated object manufacturing. The FlexAM harnesses the view angle-dependence to deliver a voltage-activated and ultrafast coloration performance at a rate of 2.814 nm ms −1 . Abstract : Structural coloration in biomimetic nanostructures has remarkable application potential in vivid display devices, but their color change effect is still insufficiently competitive towards biology. Inspired by the feather color change of a hummingbird, a new methodology for coloration is proposed. A structure-colorable flexural artificial muscle (FlexAM) is developed by integrating a view-angle dependent photonic diffraction grating pattern and voltage-actuated dielectric elastomers as an electroactive entity via laminated object additive manufacturing. A multi-physics model is developed which guides the FlexAM to harness the view-angle dependence for the new coloration strategy. The electro-mechanochromic performances are experimentally characterized to verify the prediction of the multi-physics model. An ultrafast coloration in the FlexAM with an advancing figure-of-merit at a color-shift rate of 2.814 nm ms −1 is realized, in addition to an excellent fatigue resistance up to 10 000 cycles. A photonic display with arrayed FlexAM elements is designed, which can be used to display numbers and letters. The current research offers an advanced artificial muscle towards active photonic and visible strain sensing.